Using two-dimensional correlation size exclusion chromatography (2D-CoSEC) to explore the size-dependent heterogeneity of humic substances for copper binding - Lee, Yun-Kyung; Hur, Jin (Environmental pollution (1987), 2017)
Knowledge of the heterogeneous distribution of humic substances (HS) reactivities along a continuum of molecular weight (MW) is crucial for the systems where the HS MW is subject to change. In this study, two dimensional correlation spectroscopy combined with size exclusion chromatography (2D-CoSEC) was first utilized to obtain a continuous and heterogeneous presence of copper binding characteristics within bulk HS with respect to MW. HS solutions with varying copper concentrations were directly injected into a size exclusion chromatography (SEC) system with Tris-HCl buffer as a mobile phase. Several validation tests confirmed neither structural disruption of HS nor competition effect of the mobile phase used. Similar to batch systems, fluorescence quenching was observed in the chromatograms over a wide range of HS MW. 2D-CoSEC maps of a soil-derived HS (Elliot soil humic acid) showed the greater fluorescence quenching degrees with respect to the apparent MW on the order of 12500 Da > 10600 Da > 7000 Da > 15800 Da. The binding constants calculated based on modified Stern-Volmer equation were consistent with the 2D-CoSEC results. More heterogeneity of copper binding affinities within bulk HS was found for the soil-derived HS versus an aquatic HS. The traditional fluorescence quenching titration method using ultrafiltered HS size fractions failed to delineate detailed distribution of the copper binding characteristics, exhibiting a much shorter range of the binding constants than those obtained from the 2D-CoSEC. Our proposed technique demonstrated a great potential to describe metal binding characteristics of HS at high MW resolution, providing a clear picture of the size-dependent metal-HS interactions. [Display omitted] •2D-CoSEC is first utilized to explore HS heterogeneity for metal binding.•A continuous distribution of binding constants was obtained over a wide MW range.•Metal binding of ultrafiltered HS fractions provides limited size-dependent characteristics.•2D-CoSEC proved its high-resolution detection for copper binding within bulk HS. A very wide range of size-dependent copper binding characteristics was found within bulk HS via a fluorescence quenching method combining SEC and 2D-COS.